A Decade of Liberal Cosmopolitanism in the United States: The Effects of Gender, Race, and Income - Cao, Liqun (International Journal of Criminology and Sociology, 2024)
This study investigates correlates of cosmopolitan sentiments in the United States over a decade, contributing to the literature in two ways. First, it tests the “group status thesis” in the U.S., which suggests that marginalized and disadvantaged groups are more likely to exhibit cosmopolitan attitudes. Second, it examines the interaction between socioeconomic factors and the waves of the World Values Survey conducted between 2006 and 2017. The findings support the main hypotheses of the group status thesis: women, non-Whites, and lower-income individuals tend to be more cosmopolitan in their outlook. Over the 11-year period, the gap in liberal cosmopolitanism between genders and income levels widened. The study concludes that liberal cosmopolitanism is rooted in specific structural locations, with marginalized groups being more inclined to embrace it. Notably, support for cosmopolitanism remained relatively strong before and during the early years of the Trump administration in 2017.